1998
DOI: 10.1007/s002960050031
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis and infections of the female urogenital tract

Abstract: Thirty-two female patients with confirmed ankylosing spondylitis (AS) and 33 women of similar age with pure ileitis terminalis Crohn were examined for genitourinary infection. Urethral syndrome was found in 15 out of 32 patients with AS: 11 of them had urethritis and 4 urethritis associated with vaginitis. Five women of the control group suffered from urethritis. In all cases with genitourinary infection, Chlamydia trachomatis was isolated. By comparing the AS-patients (urogenital infection group and the non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…The selective reporting of C. trachomatis in only a subset of AS patients in the first study and the lack of comparison to a control group in both studies means these results are difficult to interpret. A study of genital infections in women with AS reported a similarly high C. trachomatis rate detected by cell culture (15/32), which was significantly higher than the rate measured in controls (5/33) ( 99 ). However, a similar study performed in men with AS using sensitive molecular methods found much lower rates of C. trachomatis (1/32), which were indistinguishable from controls (3/120) ( 98 ); note that this study found high rates of C. trachomatis antibodies in these AS patients (20/32) ( 98 ), as reported earlier in this paragraph.…”
Section: The Usual Suspectsmentioning
confidence: 93%
“…The selective reporting of C. trachomatis in only a subset of AS patients in the first study and the lack of comparison to a control group in both studies means these results are difficult to interpret. A study of genital infections in women with AS reported a similarly high C. trachomatis rate detected by cell culture (15/32), which was significantly higher than the rate measured in controls (5/33) ( 99 ). However, a similar study performed in men with AS using sensitive molecular methods found much lower rates of C. trachomatis (1/32), which were indistinguishable from controls (3/120) ( 98 ); note that this study found high rates of C. trachomatis antibodies in these AS patients (20/32) ( 98 ), as reported earlier in this paragraph.…”
Section: The Usual Suspectsmentioning
confidence: 93%
“…Andererseits ist auch denkbar, dass synoviale T-Zell-Klone mit autoreaktiven u. o. kreuzreaktiven Eigenschaften proliferieren, eine chronische Arthritis unterhalten und körpereigenes Gewebe attackieren [13]. Auch bei Patienten mit länger bestehender, aktiver AS fanden sich gehäuft Hinweise auf persistierende Infektionen mit C. trachomatis [21] und Klebsiella pneumoniae [14,25,35].…”
Section: Interaktionen Zwischen Bakteriellen Erregern Makrophagen Ununclassified